Role of antimicrobial peptide cathelicidin in thrombosis and thromboinflammation - Zhang, Qing; Ul Ain, Qurrat; Schulz, Christian; Pircher, Joachim (Frontiers in Immunology, 2023)
Thrombosis is a frequent cause of cardiovascular mortality and hospitalization. Current antithrombotic strategies, however, target both thrombosis and physiological hemostasis and thereby increase bleeding risk. In recent years the pathophysiological understanding of thrombus formation has significantly advanced and inflammation has become a crucial element. Neutrophils as most frequent immune cells in the blood and their released mediators play a key role herein. Neutrophil-derived cathelicidin next to its strong antimicrobial properties has also shown to modulates thrombosis and thus presents a potential therapeutic target. In this article we review direct and indirect (immune- and endothelial cell-mediated) effects of cathelicidin on platelets and the coagulation system. Further we discuss its implications for large vessel thrombosis and consecutive thromboinflammation as well as immunothrombosis in sepsis and COVID-19 and give an outlook for potential therapeutic prospects.